DEVELOPMENT OF HIGHER EDUCATION IN UZBEKISTAN: HISTORY, CHALLENGES AND PROSPECTS - Zarnigor Alisher qizi Rajabova; Feruza Khayotovna Bobojonova (Web of Journals Publishing, 2025)
This article analyzes the key changes, reforms, stages of development, problems, and solutions in the higher education system of Uzbekistan, particularly in the Bukhara region, during the years of independence. The article also provides detailed information on the formation processes and future prospects of the national model of higher education using the example of the Bukhara region.
Keywords: Bukhara region, higher education, education reforms, quality of education, scientific potential, university, professor-teacher, bachelor, master's student, institute.